The European Union and State Building in the Western Balkans - Taylor, Andrew J. (2013)
This paper examines the feasibility of network governance in the context of the EU's expansion in the Western Balkans. The EU is formally committed to promoting network governance but the realities of enlargement require the creation of effective states, in other words of the primacy of hierarchy over network. Networks are created in enlargement and reflect the complexities of public policy but these networks do not represent, as yet, a significant shift of power away from the state. Despite a normative preference for network governance, the political reality of enlargement is that the EU seeks the creation of effective hierarchy.